Nematicidal screening of essential oils and potent toxicity of Dysphania ambrosioides essential oil against Meloidogyne incognita in vitro and in vivo. Issue 7 (21st April 2019) - Barros, Aline F.; Campos, Vicente P.; de Paula, Letícia L.; Oliveira, Denilson F.; de Silva, Fabíola J.; Terra, Willian C.; Silva, Geraldo H.; Salimena, Juliana P.
Abstract: It is known that some plant essential oils have pesticide activities. Among the 29 oils evaluated in this study, 14 showed nematicidal activities of 8 to 100% at the concentration of 1, 000 μg/ml, compared with a control of 0.01 g/ml Tween 80 ® . At a lower concentration of 500 μg/ml, only Dysphania ambrosioides oil caused >90% mortality of second‐stage juveniles (J2) of Meloidogyne incognita . The LC50 and LC95 values for D. ambrosioides oil were 307 μg/ml and 580 μg/ml, respectively. M. incognita eggs placed in D. ambrosioides oil solutions had a significant reduction in J2 hatching compared with controls. Therefore, the oil had a toxic effect on both eggs and J2 of M. incognita . This was in contrast to nematicides on the market that act efficiently only on J2. When J2 were placed in D. ambrosioides oil at its LC50 concentration and inoculated onto tomato plants, the reduction in numbers of galls and eggs was 99.5% and 100%, respectively. Dysphania ambrosioides oil applied to the potting substrate of plants at a concentration of 1, 100 μg/ml significantly reduced the number of galls and eggs of M. incognita, whereas a concentration of 800 μg/ml only reduced the number of eggs compared with the controls (Tween 80 ® and water). The main components of the D. ambrosioides oil detected by gas chromatography–mass spectrometry were ( Z )‐ascaridole (87.28%), E‐ascaridole (8.45%) and p ‐cymene (3.35%), representing 99.08% of the total oil composition. Given its nematicidal activity, D. ambrosioides oil represents an exciting raw material in the search for new bioactive molecules for the pesticide industry.